Development of Digitalization Strategies for Small and Medium-Sized Enterprises (SMEs) in Layer Poultry Farming in Baolan District Tolitoli Regency - Satria, S.; Fatmah, F. (Universitas Bengkulu, 2025)
This research was conducted to ensure that entrepreneurs engaged in egg-laying chicken farming in Tolitoli Regency, particularly in Baolan District, can effectively implement digital marketing strategies based on websites, which constitute the primary outcome of this study. An examination of the Tolitoli Regency area reveals its status as the outermost region in Indonesia, presenting a strategic opportunity for the local government to enhance the marketing efforts of SMEs. This endeavour is crucial for improving the community's economy and supporting the government's initiatives aimed at optimising the digital economy through focused research. Moreover, it represents a significant step towards addressing the development of Industrial Revolution 5.0 in Indonesia's outermost communities. This research aims to design a digital marketing strategy for the IKM website, explicitly targeting egg-laying chicken farms in Baolan District, Tolitoli Regency. The investigation was conducted directly at one of the Zoeya Berkah laying hen farms in Baolan District. The research employs the waterfall method, which entails analysis, design, development, and testing. The outcome of this research is the creation of an online sales platform for Zoeya Berkah laying hens, presented as a website that streamlines sales and marketing processes. Named Zoeya Online, this platform serves as a medium connecting small and medium-sized enterprises (SMEs) with consumers. This Business-to-Customer website offers customisation features that enable users to tailor products to their preferences, along with a purchase history that simplifies transaction tracking. Additionally, the website provides information regarding the benefits of our products and the various types of eggs available. With this platform, consumers find it easier to purchase products and are increasingly inclined to buy eggs from the Zoeya Berkah laying hen business, particularly those residing outside Baolan District.